(untitled) (Research, Society and Development, 2025)
Ketamine, traditionally used as a dissociative anesthetic, has emerged as a rapid-onset therapeutic alternative in the treatment of depressive disorders, especially in treatment-resistant cases. The objective of this study was to analyze the clinical evidence regarding the use of ketamine as both an anesthetic and an antidepressant. This is a systematic review of the literature conducted through the Virtual Health Library (VHL), using the descriptors “ketamine” AND (“depression” OR “depressive disorder” OR “major depressive disorder” OR “treatment-resistant depressive disorder”). A total of 122 publications were identified, of which 10 randomized controlled trials met the inclusion criteria. The studies demonstrate that ketamine promotes a rapid reduction in depressive symptoms, with significant effects observed within up to two hours after administration, including a decrease in suicidal ideation. Its mechanism of action involves glutamatergic modulation via NMDA receptor antagonism, promoting neuroplasticity and synaptic restoration. Additionally, ketamine presents few adverse cognitive effects and greater ease of implementation when compared to electroconvulsive therapy. However, variables such as the number of previous therapeutic failures and greater symptom severity may limit clinical response, reinforcing the need for individualized assessment. It is concluded that ketamine is an effective and rapid alternative for treatment-resistant depression, although standardization of protocols, long-term safety studies, and more robust clinical eligibility criteria are still required.